2017
DOI: 10.15666/aeer/1501_665675
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Biochemical Diversity of Hypericum Perforatum L. Grown in the Caspian Climate of Iran

Abstract: Rahnavrd: Genetic and biochemical diversity of Hypericum perforatum L.- Abstract. Hypericum perforatum, also known as St John's wort, is an important medicinal plant that produces many secondary metabolites that have anti-viral, anti-bacterial, and anti-depression properties.The most effective drug substance in this plant is hypericin that changed in the various genotypes. To investigate the genetic and biochemical diversity of Hypericum perforatum, samples were collected from different genotypes around the Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Regarding the photodynamic properties of hypericin, this metabolite has therapeutic potential as an antiviral, antiretroviral, and anticancer agent (Zhang et al, 2016, Jendželovská et al, 2016Kubin et al, 2005). Hypericin, a valuable polycyclic dianthroquinone, is responsible for the antidepression and antiviral characteristics (Rahnavrd, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the photodynamic properties of hypericin, this metabolite has therapeutic potential as an antiviral, antiretroviral, and anticancer agent (Zhang et al, 2016, Jendželovská et al, 2016Kubin et al, 2005). Hypericin, a valuable polycyclic dianthroquinone, is responsible for the antidepression and antiviral characteristics (Rahnavrd, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…After several steps emodin is made, phenolic oxidative coupling protein (Hyp-1) catalyzes the emodin anthrone production from emodin, then Hyp-1 catalyzes the emodin anthrone conversion to protohypericin, and finally, Hyp-1 catalyzes the formation of hypericin from protohypericin. Therefore the genes hyp-1, HpPKS1, and HpPKS2 are playing important roles in hypericin biosynthesis (Rahnavrd, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Administration of the ethanolic extract of the leaves remarkably ameliorated both cellular and humoral antibody response in mice (Patil et al, 2010). Rahnavard (2017) reported that few studies are available on F. carica for understanding the genome structure and its infraspecific gene-tic variation. Molecular techniques are useful tools for the investigation of genetic diversity and population structure; however, morphological and biochemical methods can be used for detecting genetic variations.…”
Section: Introductionmentioning
confidence: 99%